Sociedades hidraúlicas en los Andes: Algunas perspectivas desde Huarochirí - Gelles H., Paul (1986)
"...in those works of collective utility... the cooperation of the different isolated elements became indispensable... the material need to possess natural food products, which would ensure their well-being and prosperity, made them build, through cooperative action, works that were truly stupendous, among which the annals and irrigation dams must be considered in the first place, which furrowed the territory in considerable extensions, and which carried the waters in considerable extensions, and which carried the territory in considerable extensions, and which carried the waters to places so inaccessible that it is difficult to conceive that they have ever been realized" (Tello and Miranda 1923).